2008
DOI: 10.1111/j.1468-1331.2008.02252.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine IL‐1 beta but not IL‐1 alpha promoter polymorphism is associated with Alzheimer disease in a population from the Canary Islands, Spain

Abstract: In our population, IL-1 beta promoter polymorphism (-511 C/T) is an independent risk factor for AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…138,139 In one study, IL1B at -511 increased the odds for AD but the IL1A -889 polymorphism did not. 140 A strong association was shown between AD and IL1B +3954, but not -511 in another study. 141 Other studies have found no relation between IL1B-511 and AD.…”
Section: Interleukin-1mentioning
confidence: 97%
“…138,139 In one study, IL1B at -511 increased the odds for AD but the IL1A -889 polymorphism did not. 140 A strong association was shown between AD and IL1B +3954, but not -511 in another study. 141 Other studies have found no relation between IL1B-511 and AD.…”
Section: Interleukin-1mentioning
confidence: 97%
“…This meta-analysis proved that there is a need for future studies to confirm or exclude an association between the -511 CT polymorphism and AD. Shortly after the publication of this meta-analysis, a study on 282 Caucasian AD cases and 312 controls brought positive results regarding the association between the IL-1 ␤ -511 polymorphism and AD [14] . Meta-analysis of 16 studies with Caucasian patients on rs3087258 SNP (-511, allele T versus C effect) included in AlzGene database (http://www.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies demonstrated overexpression of IL-1 ␤ in the brain of AD patients [11,12] . Moreover, IL-1 ␤ polymorphisms responsible for higher production of the cytokine were also associated with an increased risk for AD [13,14] .…”
Section: Introductionmentioning
confidence: 99%